Composite binocular perception from dichoptic stimulus arrays with similar ensemble information - Oakyoon Cha (Nature Portfolio, 2018)
Abstract We view the world through laterally displaced eyes that generate two streams of image signals differing slightly in their perspectives of the visual scene. The brain derives three-dimensional structures from these two image streams by establishing binocular matches and computing image disparities between the two eyes’ views. Since the binocular matching problem can have multiple, alternative solutions, vision relies on several strategies to determine the most probable matches. The current study investigated whether the visual system might utilize regularities among neighbouring features (feature ensembles) when confronting this problem. We hypothesized that binocular perception with unlikely, anomalous ensembles would indicate unsuccessful binocular matches. We made dichoptic stimulus arrays of coloured circles and manipulated the colour similarity of stimulus items to produce probable or unusual ensembles when superimposed. Using binocular rivalry as a proxy index, we found that composite perception of dichoptic arrays was more stable when the stimulus items shared similar colours, and that unusual ensembles induced binocular rivalry. Our results suggest that binocular ensembles can be utilized to detect unsuccessful binocular matches, thus uncovering a potentially useful supplemental strategy for identifying binocular matches when viewing potentially confusing visual scenes containing redundant visual features.